PENANAMAN NILAI TOLERANSI BERBASIS DEEP LEARNING PADA SISWA SDN 93/III MUKAI PINTU DI ERA KEBERAGAMAN DIGITAL - Liantori, Beni; Yatim, Muhammad; Fitri, Elmina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the process of cultivating deep learning-based tolerance values in elementary school students in the context of digital diversity. The phenomenon of intolerance that is increasingly surfacing among children through digital media is an important background in this study. Using a qualitative case study approach, the research was conducted at SDN 93/III Mukai Pintu, Jambi, which has a high level of diversity. Data were collected through semi-structured interviews, participatory observation and documentation with the class teacher, principal and ten students who were actively involved in diversity-based learning. The results of thematic data analysis revealed three main themes in the process of internalizing tolerance values: (1) structured digital diversity experiences through educational visual media, (2) students' personal reflections through visual narratives such as journals and vlogs, and (3) cross-identity collaboration in digital projects that encourage interaction and empathy between students. The findings show that deep learning approach is able to integrate cognitive, affective, and social aspects in contextualized and meaningful character learning. This research makes a theoretical contribution to the development of constructivistic-humanistic approaches in character education, and offers a model of learning practices that are relevant for elementary schools in the digital era. Implications include the need for value-based micro-curriculum integration and technology, as well as teacher training in facilitating reflective and collaborative learning. Future research is recommended to test the replication of this model in different geographical contexts and education levels to broaden its applicability.